2011
DOI: 10.1007/s00411-011-0393-6
|View full text |Cite
|
Sign up to set email alerts
|

Element interactions and soil properties affecting the soil-to-plant transfer of six elements relevant to radioactive waste in boreal forest

Abstract: Cobalt (Co), lead (Pb), molybdenum (Mo), nickel (Ni), uranium (U), and zinc (Zn) are among the elements that have radioactive isotopes in radioactive waste. Soil-to-plant transfer is a key process for possible adverse effects if these radionuclides are accidentally released into the environment. The present study aimed at investigating factors affecting such transfer in boreal forest. The plant species studied were blueberry (Vaccinium myrtillus), May lily (Maianthemum bifolium), narrow buckler fern (Dryopteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…A significant negative linear relationship was found between K-Ca and K-Zn. The latter negative relationships agree with the finding of Roivainen et al (2012), who reported that the concentrations of soil macronutrients such as K, Mg and P negatively affected the uptake of several trace elements (Co, Mo, Ni, Pb, U and Zn) in boreal forests.…”
Section: Chemical and Biochemical Properties Of Norway Sprucesupporting
confidence: 82%
“…A significant negative linear relationship was found between K-Ca and K-Zn. The latter negative relationships agree with the finding of Roivainen et al (2012), who reported that the concentrations of soil macronutrients such as K, Mg and P negatively affected the uptake of several trace elements (Co, Mo, Ni, Pb, U and Zn) in boreal forests.…”
Section: Chemical and Biochemical Properties Of Norway Sprucesupporting
confidence: 82%
“…As the results for "mobile" (measured with an extraction method that provides an estimate of the fraction available to plants) and total concentrations in soil were essentially similar in our previous studies (Roivainen et al, 2011a(Roivainen et al, , 2011b(Roivainen et al, , 2012Tuovinen et al, 2011), we measured only soil total concentration in this study. Apart from concentration in soil, several factors including solid/liquid partition coefficient (Kd), pH (Echevarria et al, 2001) fertilization (Ryfyikiri et al, 2006), speciation of radionuclides (Salbu et al, 2004), interactions of elements, soil organic matter and clay contents (Roivainen et al, 2011a(Roivainen et al, , 2011b(Roivainen et al, , 2012 and rhizosphere processes (Ehlken and Kirchner, 2002), may impact the availability of elements in reality.…”
Section: Element Uptake From Soil and Plant Element Concentrationsmentioning
confidence: 81%
“…Apart from concentration in soil, several factors including solid/liquid partition coefficient (Kd), pH (Echevarria et al, 2001) fertilization (Ryfyikiri et al, 2006), speciation of radionuclides (Salbu et al, 2004), interactions of elements, soil organic matter and clay contents (Roivainen et al, 2011a(Roivainen et al, , 2011b(Roivainen et al, , 2012 and rhizosphere processes (Ehlken and Kirchner, 2002), may impact the availability of elements in reality. However, simplifications are necessary in radioecological modeling, and CRs based on total concentration are generally used.…”
Section: Element Uptake From Soil and Plant Element Concentrationsmentioning
confidence: 99%
“…Plant elements were positively correlated with soil element concentrations for seven elements in leaves and six in roots, other plant elements were negatively correlated or had no significant relationships with soil element concentrations (Appendix S9). Several published studies also detected weak coupling between soil and plant element concentrations (Ladanai et al, 2010;Roivainen et al, 2012). Soil properties (such as soil temperature, moisture, pH and Eh) and environmental factors that affected the biological availability of elements (Chapin, 1980;Kabata-Pendias, 2011;Roivainen et al, 2012), obscured to some extent the relationship between soil and plant element concentrations.…”
Section: Similar Regulation Of the Environment And Evolution On Elemementioning
confidence: 99%